KNOWLEDGE CAFÉS IN ACADEMIA: A VEHICLE FOR KNOWLEDGE SHARING - Desireé Cranfield (ICERI2021 Proceedings, 2021)
Higher Education Institutions’ academic culture can be quite hierarchical, competitive, and individualist, where the focus for advancement is very much on publishing. For new and relatively new staff, entry into the academic context can be viewed as a highly individualised, and self‐directed process. Teaching commitments, committee meetings, workload, and office hours all demand a significant amount of an academic members’ time, together with the research and scholarship activities required. Time available for informal knowledge sharing is severely restricted and opportunities for authentic and open pedagogical conversations is not often created, especially between experienced and less experience staff members. Additionally, given the pressure exerted on higher education institutions to be agile, and adapt quickly to the changing environment, knowledge sharing is critical to staff and organisation’s agility. It is also important for academics to embrace continuous learning; however, the nature of academia can make knowledge sharing challenging. Research suggests that engaging in knowledge sharing activities improves outcomes. A pilot case study was conducted at a Welsh university to implement three Knowledge Cafe’s over a period of 1 ½ years. The aim of the Knowledge Cafés were to bring people together to engage in a shared and purposeful activity (teaching practice in this case), informally over coffee, conversing around a particular topic of interest, which enables each staff member to reflect on their own practice, share experiences, and evaluate the effectiveness of their own teaching. A specific format for the Knowledge Café is used to encourage engagement and informal conversation, in an environment of openness. Initial outcomes suggests that creating opportunities for the sharing of teaching best practices using a Knowledge Café creates a positive, informal ‘space’ for knowledge sharing, however, the timing of these opportunities is critical, and the question and external speaker, and leadership support give credence to the sessions.